High-toughness austenite transformation induced plasticity alloy and preparation method thereof

The introduction of dislocation and layer-error structures through pre-deformation treatment has solved the problem of insufficient hardening ability of austenite phase change-induced plastic alloys in the early stage of deformation, significantly improved their tensile strength, elongation and strong plasticization, and achieved high performance austenite phase transition-induced plastic alloy, suitable for the automotive industry.

CN119307826APending Publication Date: 2025-01-14CENT OF EXCELLENCE FOR ADVANCED MATERIALS +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411438108.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing austenite phase transition-induced plastic alloys have insufficient work hardening capabilities in the early stage of deformation and have a long incubation period, which leads to the improvement of the deformation ability, elongation and strong plastic accumulation of the material, making it difficult to meet the high-performance materials needs of the automobile industry.

Method used

Dislocation and layered structure are introduced through pre-deformation treatment, providing nucleation sites for martensite phase transformation, allowing the alloy to directly enter the strain hardening stage through the incubation period of phase transformation, enhancing the strengthening effect of the TRIP effect, and improving the The tensile strength, elongation and strong plasticization of the material.

Benefits of technology

It significantly improves the tensile strength, elongation and strong plasticization of the alloy, enhances its strong plasticity, and obtains a high-performance austenite phase change-induced plastic alloy, which is suitable for the automotive industry and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0005085632980000011
    Figure HDA0005085632980000011
  • Figure HDA0005085632980000012
    Figure HDA0005085632980000012
Patent Text Reader

Abstract

The invention relates to a high-toughness austenite transformation induced plasticity alloy and a preparation method thereof. The high-strength and high-toughness austenite transformation-induced plasticity alloy has the remarkable transformation-induced plasticity strengthening characteristic, and meanwhile, the good mechanical property and room-temperature forming capacity are shown. The preparation method of the alloy comprises the steps of ingredient smelting, hot rolling, acid pickling, cold rolling, annealing, leveling and pre-deformation treatment, dislocation, stacking dislocation and other structures are introduced through pre-deformation, nucleation sites are provided for martensite phase transformation, the alloy can directly enter the strain hardening stage across the inoculation period needed by phase transformation, and the alloy quality is improved. And meanwhile, the alloy material is controlled to be subjected to pre-deformation treatment within a certain pre-deformation range, the mechanical property of an existing alloy material can be effectively improved, the strengthening and toughening effect of the TRIP effect is enhanced, and a high-performance new material is obtained. Meanwhile, the preparation method is simple, convenient and easy to industrialize, and can be widely applied to preparation of high-performance alloys of different systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal materials, and in particular to a high-strength and tough austenite transformation-induced plasticity alloy and a preparation method thereof. Background Art

[0002] In recent years, the automobile industry has developed rapidly, and the number of cars in use has been on the rise. Energy saving, environmental protection, safety, and comfort have become the new direction of the development of the automobile industry, which has put forward higher requirements for car body materials. Transformation induced plasticity (TRIP) alloy is a high-strength material with good plasticity and toughness, which can be used in the manufacture of equipment such as automobile bodies to ensure safety. TRIP alloys based on austenite have good formability, corrosion resistance, and good comprehensive mechanical properties. During the processing and deformation process, the soft austenite is transformed into hard martensite through phase transformation, which significantly improves the strength of the alloy. However, a certain stress and strain level is usually required to induce martensitic phase transformation, that is, there is a "gestation period" for martensitic phase transformation, which makes the material's work hardening ability insufficient at the initial stage of deformation; and when austenite is completely transformed into martensite, the material loses its deformation ability and breaks quickly, and its elongation and strength-ductility product need to be improved. How to optimize the mode of action of martensitic phase transformation strengthening and obtain the structural design and performance regulation method of high-performance TRIP alloys is the key to preparing high-performance materials suitable for the automotive industry and other fields.

[0003] In the prior art, the patent with application number CN202011485343.3 discloses an austenitic stainless steel for nuclear power valves and a preparation method thereof. The composition of the stainless steel is C≤0.08%, Si≤0.8%, Mn≤2.00%, S≤0.02%, P≤0.03%, Cr: 17.0~19.0%, Ni: 9.0~12.0%, Co≤0.08%, Ti≥5×C%; the provided material has a large elongation and high impact absorption work, but its strength is low, and the cyclic forging process is complicated and difficult to operate, and the production efficiency is low.

[0004] The patent with application number 202210025931.1 discloses an austenitic stainless steel, a preparation method thereof and an application in a hydrogen storage pressure vessel. The steel plate composition is (wt.%): C: 0.010%~0.030%, Si: 0.40%~0.75%, Mn: 1.3%~2.0%, Cr: 17.5%~18.0%, Ni: 13.05%~14.00%, Mo: 2.5%~3.0%, P≤0.030%, S≤0.002%, N≤0.06%, Cu≤0.5%, B: 0.002%~0.005%, ensuring Nieq: 28.5~35, and the rest is Fe and unavoidable impurities; although the steel plate provided by it has a high elongation after fracture, the strength is insufficient, and the addition of the Mn element will inevitably make the continuous casting process difficult, and its complex alloy element composition is not conducive to the recycling of materials.

[0005] The patent with application number 201811049467.X discloses an ultra-high strength and toughness medium manganese phase transformation induced plasticity steel and its preparation method. The composition of the material is (wt.%): C: 0.35%~0.36%, Mn: 4.5%~7.5%, Al: 3.2%, P<0.007%, S<0.03%, and the balance is Fe. The preparation process includes smelting, forging, hot rolling, cold rolling, and then two-phase annealing + low-temperature tempering; although the steel plate provided has good mechanical properties, the phase structure and mechanical properties of the material are sensitive to annealing and tempering parameters, and the processing process needs to be strictly controlled to obtain the ideal material.

[0006] The patent application number 202310013683.3 discloses the application of boron (B) element in improving the strength and corrosion resistance of super austenitic stainless steel. The key is to use B microalloying combined with aging treatment to obtain a dispersed nanoscale precipitation phase; this method is suitable for strengthening materials with second phase precipitation, and has limited strengthening effect on materials with single-phase solid solution structure.

[0007] It can be seen that the mode of action of the TRIP effect is closely related to the mechanical properties of the alloy. Therefore, it is crucial to optimize the comprehensive performance of TRIP alloys and how to regulate the mode of action of the TRIP strengthening effect. Summary of the invention

[0008] Based on this, the purpose of the present invention is to provide a high-strength and tough austenitic phase transformation induced plasticity alloy, which has the characteristics of significant phase transformation induced plastic strengthening, and at the same time exhibits good mechanical properties and room temperature forming ability. It can effectively solve the problems of the long incubation period required for the induced phase transformation of existing alloys, insufficient tensile plasticity, and the need to improve the strength-plasticity product, and can be widely used in the automotive industry and other fields as a high-performance material.

[0009] Another object of the present invention is to provide a method for preparing a high-strength and tough austenitic transformation-induced plasticity alloy, wherein the flattened plate is pre-deformed to introduce structures such as dislocations and stacking faults, thereby providing nucleation sites for martensitic transformation, allowing the alloy to skip the "incubation period" required for the phase transformation and directly enter the strain hardening stage, thereby enhancing the strengthening and toughening effect of the TRIP effect and obtaining a high-performance new material.

[0010] A high-strength and tough austenite transformation-induced plasticity alloy, comprising the following components in percentage by mass:

[0011] Fe: 67~73%, Cr: 18~24%, Ni: 8~14%.

[0012] Furthermore, the alloy has a tensile strength of 810-860 MPa, an elongation of 21-25%, and a strength-ductility product of 16-20 GPa·%. Compared with conventional high-strength and tough austenite transformation-induced plasticity alloys, the tensile strength, elongation, and strength-ductility product of the alloy provided by the present invention are significantly improved, and its strength and ductility are significantly improved.

[0013] A method for preparing a high-strength and high-toughness austenite transformation-induced plasticity alloy comprises the following steps:

[0014] S1: Weighing alloy raw materials according to proportion and putting them into a melting furnace for vacuum melting, and then casting them into ingots;

[0015] S2: hot rolling the ingot obtained in step S1 to obtain a hot-rolled plate, and cooling it to room temperature;

[0016] S3: The hot-rolled plate is pickled to remove the oxide layer; the surface of the plate is then polished to remove impurities, and then cleaned with anhydrous ethanol and dried;

[0017] S4: cold rolling the hot rolled sheet processed in step S3 to obtain a cold rolled sheet;

[0018] S5: annealing the cold rolled sheet;

[0019] S6: Smoothing the annealed sheet;

[0020] S7: Pre-deformation treatment, the pre-deformation amount of the pre-deformation is ≤5%.

[0021] The present invention provides a method for preparing a high-strength and tough austenite transformation-induced plasticity alloy, which introduces structures such as dislocations and stacking faults through pre-deformation treatment to provide nucleation sites for martensitic phase transformation, so that the alloy can directly enter the strain hardening stage by skipping the "incubation period" required for the phase transformation to occur, thereby enhancing the strengthening and toughening effect of the TRIP effect. On the one hand, it can effectively improve the work hardening rate of the alloy in the early stage of deformation, and on the other hand, it can extend the strain range of martensitic phase transformation strengthening, thereby improving the tensile plasticity and strength-plasticity product of the material.

[0022] Furthermore, in step S1, the ingot obtained by smelting is homogenized, the homogenization temperature is 1200±10°C, the heating rate is 8-12°C / s, the homogenization time is 180-240min, and the cooling rate after homogenization is 2-4°C / s

[0023] Furthermore, in step S2, the hot rolling treatment conditions are as follows: heating the ingot to a hot rolling temperature of 1150±30°C, a heating rate of 8-12°C / s, and keeping warm for 100-120 minutes; then a double-roll hot rolling mill is used for multiple passes of rolling, the starting rolling temperature is 1150±10°C, the rolling amount per pass is 3-5%, the total rolling amount is 30-40%, and the final rolling temperature is 950±30°C to obtain the hot-rolled plate.

[0024] Furthermore, the thickness of the hot-rolled plate is 9 to 11 mm.

[0025] Furthermore, in step S3, the hot-rolled plate is pickled for 20 minutes using a 1:3 hydrochloric acid solution to remove the oxide layer.

[0026] Furthermore, in step S4, the cold rolling process adopts a four-roller cold rolling mill, and the cold rolling process conditions are that the rolling amount per pass is 3-5%, and the total rolling amount is 70-80%.

[0027] Furthermore, the cold-rolled sheet has a sheet thickness of 0.8 to 2.2 mm.

[0028] Furthermore, in step S5, the annealing temperature is 600-800°C, the heating rate is 8-12°C / s, the temperature is kept for 10-60 minutes, and then cooled to room temperature.

[0029] Furthermore, in step S6, the elongation of the flattening treatment is 0.5-1.2%.

[0030] Furthermore, the thickness of the plate obtained after the flattening treatment is 0.6 to 2 mm.

[0031] Furthermore, in step S7, the thickness of the finished plate obtained by the pre-deformation treatment is 0.4 to 1.8 mm.

[0032] Furthermore, the pre-deformation treatment is a stretching method; it is understandable that the pre-deformation methods include but are not limited to: stretching, rolling, extrusion, forging, etc.

[0033] Furthermore, the matrix structure of the alloy before stretching includes 90-100% austenite by volume; and the matrix structure of the alloy after stretching includes 90-100% martensite by volume. It can be seen that the preparation method of a high-strength and tough austenite transformation-induced plasticity alloy provided by the present invention introduces structures such as dislocations and stacking faults into the matrix through a low-deformation pre-deformation treatment, providing nucleation sites for the subsequent formation of martensitic phases, so that the alloy can directly enter the TRIP strengthening stage by skipping the "incubation period" of the martensitic phase transformation during the processing deformation process, thereby enhancing the strengthening and toughening effect of the TRIP effect and obtaining a high-performance alloy material.

[0034] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the EBSD morphology image of the plate before pre-deformation treatment in Example 1.

[0036] Figure 2 This is the phase distribution diagram of the plate before pre-deformation treatment in Example 1.

[0037] Figure 3 This is the uniaxial tensile engineering stress-strain curve of Example 1.

[0038] Figure 4 This is the uniaxial tensile engineering stress-strain curve of comparative example 1. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] A high-strength and tough austenite transformation-induced plasticity alloy and a preparation method thereof, first using Thermal-Cal software and TCFE7 database to calculate the transformation temperatures of ferrite, austenite and martensite of alloys with different components under the equilibrium phase diagram, determine the element ratio, homogenization treatment, hot rolling, annealing temperature parameters, and determine the mass percentage of the main elements of the alloy. Perform the following steps in sequence:

[0041] S1: Fe, Cr, and Ni alloy raw materials with a purity of ≥99.9% are weighed according to the chemical composition ratio of the alloy, mixed evenly, and then transferred to a melting crucible. Then, the mixed alloy raw materials are placed in an induction melting furnace, vacuum melted under argon protection, and then the molten steel is cast into an ingot; the ingot is homogenized at a homogenization temperature of 1200±10℃, a heating rate of 8-12℃ / s, a homogenization time of 180-240min, and a cooling rate of 2-4℃ / s after homogenization.

[0042] S2: The ingot at room temperature is heated to the hot rolling temperature of 1150±30°C by hot charging method, the heating rate is 8-12°C / s, and the heat preservation time is 100-120min; then multiple rolling is carried out, the starting rolling temperature is 1150±10°C, the rolling amount of each pass is 3-5%, the total rolling amount is 30-40%, the final rolling temperature is 950±30°C, and the hot rolled plate with a thickness of 10mm is obtained; after hot rolling, the hot rolled plate is air cooled to room temperature.

[0043] S3: The hot-rolled plate is pickled for 20 minutes using a 1:3 hydrochloric acid solution to remove the oxide layer; after pickling, the surface of the plate is polished and decontaminated, and then cleaned and dried using anhydrous ethanol.

[0044] S4: cold rolling the hot rolled plate, with each rolling amount being 3-5% and the total rolling amount being 70-80%, to obtain a plate with a thickness of 0.8-2.2 mm.

[0045] S5: annealing the cold-rolled sheet at a temperature of 600 to 800° C., a heating rate of 8 to 12° C. / s, keeping the temperature for 10 to 60 minutes, and then cooling to room temperature.

[0046] S6: flattening the annealed sheet, with a flattening elongation of 0.5-1.2%; after flattening, a sheet with a thickness of 0.6-2 mm is obtained.

[0047] S7: The flattened plate is processed at a rate of 10 -3 / s tensile pre-deformation treatment, the pre-deformation amount is ≤5%, and it is completely unloaded after stretching.

[0048] Example 1

[0049] (1) Fe, Cr, and Ni alloy raw materials with a purity of ≥99.9% are weighed according to the mass percentage of Fe: 67.5%, Cr: 18.5%, and Ni: 14%, mixed evenly, and then transferred to a melting crucible, and then the mixed alloy raw materials are placed in an induction melting furnace, vacuum melted under argon protection, and then the molten steel is cast into an ingot; the ingot is homogenized at a temperature of 1200°C and a heating rate of 10°C / s; after heating to the target temperature, the ingot is kept warm for 240 minutes, and the cooling rate after the homogenization treatment is 4°C / s.

[0050] (2) The ingot at room temperature is heated to a hot rolling temperature of 1150°C by a hot charging method, the heating rate is 10°C / s, and the temperature is kept for 100 min; multiple rolling is performed on a rolling mill, the starting rolling temperature is 1150°C, the rolling amount of each pass is 5%, the total rolling amount is 30%, and the final rolling temperature is 950°C to obtain a hot rolled plate with a thickness of 10 mm; after hot rolling, the hot rolled plate is air cooled to room temperature.

[0051] (3) The hot-rolled plate was pickled for 20 minutes using a 1:3 hydrochloric acid solution to remove the oxide layer; after pickling, the surface of the plate was polished and decontaminated, and then cleaned with anhydrous ethanol and dried.

[0052] (4) The hot-rolled plate is cold-rolled, with each pass having a rolling amount of 3% and a total rolling amount of 80%, to obtain a plate with a thickness of 2 mm.

[0053] (5) The cold-rolled sheet was annealed at 700°C, with a heating rate of 10°C / s, for 60 min, and then cooled to room temperature.

[0054] (6) The annealed plate is flattened, and the flattening elongation is 1.0%; after flattening, the sample is polished to obtain a plate A1 with a thickness of 1.8 mm.

[0055] (7) The flattened plate is processed at a rate of 10 -3 / s stretching pre-deformation treatment, the total pre-deformation amount is 3.5%, and after stretching, it is completely unloaded to obtain the pre-deformed plate B1.

[0056] The microstructure of sheet A1 before pre-deformation treatment is as follows Figure 1 and Figure 2 As shown in the figure, the uniaxial tensile engineering stress-strain curves of the plate before and after pre-deformation treatment are as follows: Figure 3 shown.

[0057] Example 2

[0058] The difference between Example 2 and Example 1 is that the composition of the alloy raw material is: Fe: 73%, Cr: 19%, Ni: 8%; the pre-deformation amount during the pre-deformation process is 5%.

[0059] In Example 2, the plate A2 is obtained after flattening; then A2 is stretched to obtain the pre-deformed plate B2.

[0060] Example 3

[0061] The only difference between Example 3 and Example 1 is that the composition of the alloy raw material is: Fe: 67%, Cr: 24%, Ni: 9%.

[0062] In Example 3, the plate A3 is obtained after flattening; then A2 is stretched to obtain the pre-deformed plate B3.

[0063] Example 4

[0064] The only difference between Example 4 and Example 1 is that the composition of the alloy raw materials is: Fe: 67.8%, Cr: 18.2%, Ni: 14%.

[0065] In Example 4, the plate A4 is obtained after flattening; then A2 is stretched to obtain the pre-deformed plate B4.

[0066] Comparative Example 1

[0067] The alloy composition used in Comparative Example 1 is the same as that in Example 1. The difference between the preparation methods of Comparative Example 1 and Example 1 is that in Comparative Example 1, the flattened plate is subjected to a heating rate of 10 -3 / s tensile pre-deformation treatment, the total pre-deformation amount is 12%, and it is completely unloaded after stretching. After the pre-deformation treatment, a plate C1 with a thickness of 1.7 mm is obtained.

[0068] Comparative Example 2

[0069] The alloy composition used in Comparative Example 2 is the same as that in Example 2. The difference between the preparation methods of Comparative Example 2 and Example 2 is that in Comparative Example 2, the flattened plate is subjected to a heating rate of 10 -3 / s tensile pre-deformation treatment, the total pre-deformation amount is 6%, and it is completely unloaded after stretching. After the pre-deformation treatment, a plate C2 with a thickness of 1.7 mm is obtained.

[0070] Comparative Example 3

[0071] The alloy composition used in Comparative Example 3 is the same as that in Example 3. The difference between the preparation methods of Comparative Example 3 and Example 3 is that in Comparative Example 3, the flattened plate is subjected to a heating rate of 10 -3 / s tensile pre-deformation treatment, the total pre-deformation amount is 12%, and it is completely unloaded after stretching. After the pre-deformation treatment, the plate C3 with a thickness of 1.7 mm is obtained.

[0072] Comparative Example 4

[0073] The alloy composition used in Comparative Example 4 is the same as that in Example 4. The difference between the preparation methods of Comparative Example 4 and Example 4 is that in Comparative Example 4, the flattened plate is subjected to a heating rate of 10 -3 / s tensile pre-deformation treatment, the total pre-deformation amount is 12%, and it is completely unloaded after stretching. After the pre-deformation treatment, the plate C4 with a thickness of 1.7 mm is obtained.

[0074] test

[0075] The plate samples obtained in Examples 1-4 and Comparative Examples 1-4 were subjected to relevant mechanical property tests, and the test methods were all carried out using existing methods, which will not be described in detail here.

[0076] Table 1 Mechanical properties test data of the plate samples obtained from Examples 1-4 and Comparative Examples 1-4

[0077]

[0078] Combination Figure 1-4 , and Table 1, from Figure 1 and Figure 2 It can be seen that the typical structure of the alloy after annealing of the plate A1 obtained in Example 1 is a completely recrystallized annealed equiaxed crystal structure with an average grain size of 1.5 microns. At this time, the matrix structure is mainly austenite, and the volume fraction of austenite (i.e., the gray area in the figure) is 98%, and the volume fraction of martensite (i.e., the white area in the figure) is 2%. This shows that when the grain size of the austenite matrix is ​​greater than 1 micron, it is conducive to stimulating the martensitic phase transformation.

[0079] Combining Table 1 and Figure 1-3 The alloy plates prepared in Examples 1-4 have significant characteristics of phase transformation-induced plastic strengthening. The matrix structure is mainly austenite. During the deformation process, austenite undergoes martensitic transformation. The synergistic strengthening effect of austenite and martensite in this process makes the tensile strength of the material reach 770-810MPa, the elongation reaches 16-20%, and the strength-plasticity product reaches 12-16GPa·%. The alloy exhibits good mechanical properties and room temperature forming ability. After pre-deformation treatment with a low pre-deformation amount, the tensile strength, elongation, and strength-plasticity product of the alloy are further increased to 810-860MPa, 21-25%, and 16-20GPa·%, and its strength and plasticity are significantly improved.

[0080] Combination Figure 3As shown in Table 1, the tensile strength, elongation, and strength-ductility product of the alloy before pre-deformation treatment in Example 1 are 800 MPa, 18%, and 14.3 GPa·%, respectively. After pre-deformation treatment with a pre-deformation amount of 3.5%, the alloy is subjected to uniaxial tensile test again. At this time, the tensile strength, elongation, and strength-ductility product of the alloy are significantly improved, reaching 810 MPa, 23.5%, and 19.1 GPa·%, respectively, showing a better strength-ductility match. Figure 4 It can be seen that the pre-deformation treatment with a higher pre-deformation amount increases the tensile strength of the alloy to about 900MPa, with a significant strengthening effect; but at this time its elongation drops to about 12.9%, and the strength-plasticity product is only 11.6GPa·%. It can be seen that the pre-deformation treatment with a high deformation amount is not conducive to obtaining a material with good strength-plasticity matching.

[0081] Combined with Table 1, it can be seen from the test data of the alloy plates obtained from Examples 1-4 that, for alloy materials within a certain component range, the tensile strength, elongation, and strength-ductility product of the alloy plates before pre-deformation treatment are relatively low. After a relatively low pre-deformation treatment, the tensile strength, elongation, and strength-ductility product of the plates are improved. It can be seen that pre-deformation treatment within a certain pre-deformation range can improve the mechanical properties of the alloy. Compared with Comparative Examples 1-4, it can be seen that when the pre-deformation amount of the pre-deformation treatment is too high, the elongation and strength-ductility product of the alloy plates drop sharply, and the mechanical properties exhibited by the alloy material are relatively poor. It can be seen that the preparation method provided by the present invention can effectively improve the comprehensive performance of austenitic TRIP alloys and obtain high-strength and toughness TRIP alloys.

[0082] Compared with the prior art, the present invention has the following beneficial effects:

[0083] (1) By strictly controlling the alloy composition and processing technology, adjusting the grain size, volume fraction and phase stability of the austenite matrix, and introducing structures such as dislocations and stacking faults through pre-deformation, nucleation sites are provided for the martensitic phase transformation, so that the alloy can skip the "incubation period" required for the phase transformation and directly enter the strain hardening stage, thereby enhancing the strengthening and toughening effect of the TRIP effect and obtaining a high-performance new material.

[0084] (2) By studying the pre-deformation amount during the pre-deformation process, the pre-deformation treatment of the alloy material within a certain pre-deformation amount range can effectively improve the mechanical properties of the existing alloy material;

[0085] (3) The preparation method provided by the present invention comprises eight steps including batch melting, hot rolling, pickling, cold rolling, annealing, flattening and pre-deformation treatment. The operation is simple and convenient, and it is easy for industrial production. It can be widely used in the preparation of high-performance alloys of different systems, and has important guiding significance and reference value for obtaining high-performance TRIP alloys.

[0086] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.

Claims

1. A high-strength and tough austenite transformation-induced plasticity alloy, characterized in that: It includes the following components in percentage by mass: Fe: 67~73%, Cr: 18~24%, Ni: 8~14%.

2. The high strength and toughness austenite transformation induced plasticity alloy according to claim 1, characterized in that: The alloy has a tensile strength of 810-860 MPa, an elongation of 21-25%, and a strength-ductility product of 16-20 GPa·%.

3. A method for preparing a high-strength and tough austenite transformation-induced plasticity alloy, comprising the following steps: S1: Weigh the alloy raw materials according to the proportion and put them into the melting furnace for vacuum melting, then cast them into ingots and perform homogenization treatment; S2: hot rolling the ingot obtained in step S1 to obtain a hot-rolled plate, and cooling it to room temperature; S3: The hot-rolled plate is pickled to remove the oxide layer; the surface of the plate is then polished to remove impurities, and then cleaned with anhydrous ethanol and dried; S4: cold rolling the hot rolled sheet processed in step S3 to obtain a cold rolled sheet; S5: annealing the cold rolled sheet; S6: Smoothing the annealed sheet; S7: Pre-deformation treatment, the pre-deformation amount of the pre-deformation is ≤5%.

4. The method for preparing a high-strength and tough austenite transformation-induced plasticity alloy according to claim 3, characterized in that: In step S1, the ingot is homogenized at a temperature of 1200±10°C, a heating rate of 8-12°C / s, a homogenization time of 180-240 min, and a cooling rate of 2-4°C / s after homogenization.

5. The method for preparing a high-strength and tough austenite transformation-induced plasticity alloy according to claim 3, characterized in that: In step S2, the hot rolling treatment conditions are as follows: heating the ingot to a hot rolling temperature of 1150±30°C, a heating rate of 8-12°C / s, and keeping warm for 100-120 minutes; then performing multiple rolling passes, with a starting rolling temperature of 1150±10°C, a rolling amount of 3-5% per pass, a total rolling amount of 30-40%, and a final rolling temperature of 950±30°C to obtain the hot rolled plate.

6. The method for preparing a high-strength and tough austenite transformation-induced plasticity alloy according to claim 3, characterized in that: In step S4, the cold rolling treatment is performed under the conditions that the rolling amount per pass is 3-5% and the total rolling amount is 70-80%.

7. The method for preparing a high-strength and tough austenite transformation-induced plasticity alloy according to claim 3, characterized in that: In step S5, the annealing temperature is 600-800°C, the heating rate is 8-12°C / s, the temperature is kept for 10-60 minutes, and then cooled to room temperature.

8. The method for preparing a high-strength and tough austenite transformation-induced plasticity alloy according to claim 3, characterized in that: In step S6, the flattening treatment elongation is 0.5-1.2%.

9. The method for preparing a high-strength and tough austenite transformation-induced plasticity alloy according to claim 3, characterized in that: In step S7, the pre-deformation treatment is one or more of stretching, rolling, extrusion and forging.

10. The method for preparing a high-strength and tough austenite transformation-induced plasticity alloy according to claim 9, characterized in that: The pre-deformation treatment is a stretching method; before the stretching, the matrix structure of the alloy includes 90-100% austenite by volume; after the stretching, the matrix structure of the alloy includes 90-100% martensite by volume.

Citation Information

Patent Citations

  • Ultra-high strength and toughness manganese phase transformation induced plasticity steel and its preparation method

    CN108998741B

  • A method for preparing austenitic stainless steel for nuclear power plant valves

    CN112680664B

  • Austenitic stainless steel, preparation method thereof and application of austenitic stainless steel in hydrogen storage pressure vessel

    CN114351051A

  • Application of B element in improving strength and corrosion resistance of super austenitic stainless steel

    CN116005073A